A Dermatological Intervention of Gynecomastia in Young Asian Man with a History of Soy Product Consumption: A Case Report - Widjajahakim R; Widjajahakim RM; Winaya KK (International Medical Case Reports Journal)
Reyhan Widjajahakim,1 Raymond Makmur Widjajahakim,1 Ketut Kwartantaya Winaya2 1Raymond Skin Clinic, Pekanbaru, Riau, Indonesia; 2Department of Dermatology and Venereology, Faculty of Medicine, Udayana University/Prof. Dr. I.G.N.G Ngoerah General Hospital, Denpasar, Bali, IndonesiaCorrespondence: Ketut Kwartantaya Winaya, Department of Dermatology and Venereology, Faculty of Medicine, Udayana University/Prof. Dr. I.G.N.G Ngoerah General Hospital, Dauh Puri Klod, Denpasar, Bali, 80113, Indonesia, Tel +62811399796, Email dr.kwartantayaw@unud.ac.idAbstract: Gynecomastia is an enlargement of the breasts in men, which is usually benign but can also manifest as a result of malignancies, and can be either unilateral or bilateral. Pseudogynecomastia is male breast enlargement due to excessive fat, while true gynecomastia is a proliferation of glandular tissue. Gynecomastia is common in infants, adolescents, and elderly men, with the most common cause is related to hormonal changes associated with aging. Medical intervention is usually required for true gynecomastia that has lasted more than a year. Here, we report a case of a 33-year-old Chinese-Indonesian decent with enlarged breasts. The patient reported frequent consumption of homemade soybean milk (1/2 to 1 liter daily) accompanied by bland chicken during his body-building regimen. The patient had discontinued the regimen and the diet for 2 years prior to the initial visit. During physical examination, both breasts were enlarged and had firm nodule, mobile, and attached at the sub-central areola mammae with a diameter of 8 cm. The patient was then diagnosed with true gynecomastia Simon degree 2A and Geschikter and Copeland type 3. As the gynecomastia had persisted longer than a year, a dermatological intervention was planned. Ultrasound-assisted liposuction was performed with a solid probe and glandular excision. Fat tissue was obtained, 130 mL from the right breast and 120 mL from the left breast. A dense 2.5 cm × 2.5 cm × 2 cm glandular tissue was obtained from both breasts. The patient was satisfied with the surgery outcome.Keywords: Asian, gynecomastia, soy product consumption, surgical treatment, ultrasound-assisted liposuction